The Study of a Battery Energy Storage System Based on the Hexagonal Modular Multilevel Direct AC/AC Converter (Hexverter) - Chong Zhang; Daozhuo Jiang; Xuan Zhang; Jiaxi Chen; Chuang Ruan; Yiqiao Liang (IEEE Access)
This paper studies a battery energy storage system based on the hexagonal modular multilevel direct ac/ac converter with focus on a control method for state-of-charge (SOC) balancing of the battery units. First, the system structure and the operating principle of the hexagonal multilevel converter, including the branch voltage and the power, are analyzed and simulated, respectively. Then, the mathematical model of the energy storage submodule consisting of the battery energy storage unit and H-bridge submodule cell is developed in PSCAD/EMTDC software. After that, a SOC balancing control strategy is proposed, including the branch SOC balancing between the converter’s six branches and the individual SOC balancing between the 14 cascaded converter cells in each branch, which is realized by controlling currents in branch modules. Currents in the branches are controlled by the internal model principle. Finally, the effectiveness of the control strategy is verified in simulation.